2001
DOI: 10.1054/bjoc.2001.2097
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer risk: associations with ultraviolet radiation, tyrosinase and melanocortin-1 receptor genotypes

Abstract: Exposure to ultraviolet radiation may reduce prostate cancer risk, suggesting that polymorphism in genes that mediate host pigmentation will be associated with susceptibility to this cancer. We studied 210 prostate cancer cases and 155 controls to determine whether vitamin D receptor (VDR, Taql and Fokl variants), tyrosinase (TYR, codon 192 variant) and melanocortin-1 receptor (MC1R, Arg151Cys, Arg160Trp, Val92Met, Asp294His and Asp84Glu variants) genotypes are associated with risk. UV exposure was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 24 publications
2
43
1
Order By: Relevance
“…G 2560+9 -C 3944 was also associated with BCC risk in subjects with high and low levels of exposure to UVR. Interestingly, studies in prostate cancer patients have shown that the association of both tyrosinase and vitamin D receptor variants with risk is mediated by the extent of exposure to UVR (Luscombe et al 2001b;Bodiwala et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…G 2560+9 -C 3944 was also associated with BCC risk in subjects with high and low levels of exposure to UVR. Interestingly, studies in prostate cancer patients have shown that the association of both tyrosinase and vitamin D receptor variants with risk is mediated by the extent of exposure to UVR (Luscombe et al 2001b;Bodiwala et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that only used PSA level or bone scan to assess prostate cancer stage were excluded, as these are not valid or reliable methods for cancer staging (n = 2 studies; refs. 39,40). No articles were excluded based on language.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Hence, they concluded that susceptibility to prostate cancer is associated with an interaction between host predisposition and sun exposure. 122 …”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%